2022
DOI: 10.3389/fcell.2022.982549
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding protein signaling in adult neurogenesis

Abstract: The process of neurogenesis in the brain, including cell proliferation, differentiation, survival, and maturation, results in the formation of new functional neurons. During embryonic development, neurogenesis is crucial to produce neurons to establish the nervous system, but the process persists in certain brain regions during adulthood. In adult neurogenesis, the production of new neurons in the hippocampus is accomplished via the division of neural stem cells. Neurogenesis is regulated by multiple factors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 118 publications
(293 reference statements)
0
13
0
Order By: Relevance
“…Previous studies have shown that Fxr2 is involved in numerous neurological diseases [ 47 49 ]. Fxr2 participates in regulating gene expression changes and post-transcriptional processes, playing an essential role in neurogenesis and the regulation of adult neural stem cell self-renewal and maintenance [ 50 , 51 ]. Through actinomycin D and RIP experiments, we confirmed that Fxr2 could bind to Atf3 and reduce Atf3 mRNA stability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Fxr2 is involved in numerous neurological diseases [ 47 49 ]. Fxr2 participates in regulating gene expression changes and post-transcriptional processes, playing an essential role in neurogenesis and the regulation of adult neural stem cell self-renewal and maintenance [ 50 , 51 ]. Through actinomycin D and RIP experiments, we confirmed that Fxr2 could bind to Atf3 and reduce Atf3 mRNA stability.…”
Section: Discussionmentioning
confidence: 99%
“…When examined further, DEX is often involved in signaling pathways that are activated under oxidative stress and triggered by various stressors [ 127 ]. Additionally, what is worth mentioning are microRNAs (miRNAs), which play an important role in post-transcriptional gene regulation [ 128 ]. Many known miRNAs exist in the brain, some of them exclusively in neuronal tissue [ 129 ], and in DEX-affected miRNAs with demonstrated neuroprotection [ 130 , 131 ].…”
Section: Discussionmentioning
confidence: 99%
“…As during development, both RBPs [ 7 , 112 ] and ncRNAs [ 53 , 54 , 55 , 56 , 113 , 114 , 115 , 116 ] are responsible for all the different steps of these regulatory events. Among these latter molecules, some small nucleolar RNAs (snoRNAs) also seem to play a role in learning and memory [ 117 ].…”
Section: Post-transcriptional Regulation and Synaptic Plasticity In T...mentioning
confidence: 99%